POTENTIAL OF ORNAMENTAL FISH CULTIVATION IN AQUAPONIC SYSTEMS (LITERATURE REVIEW) - Nugraha, Zidan Fachriza Adya; Andriani, Yuli; Subhan , Ujang; Zidni, Irfan (Jurnal Perikanan Unram, 2025)
Indonesia ornamental fish industry is experiencing increasing popularity, demonstrated by a 1.99% rise in production in the first quarter of 2024 compared to the first quarter of 2023. The intensive fish farming system is a method that applies high density and provides artificial feed that has high protein to support optimal fish growth. Aquaponics is a cultivation system that can save water usage by up to 97% compared to conventional methods. This system also maintains water quality through synergistic interactions between fish and plants, creating a more productive environment. The purpose of this study was to determine the potential of various ornamental fish that can be cultivated in the aquaponic system. Based on the results obtained regarding ornamental fish cultivated in the aquaponic system, there are several types of ornamental fish that have been cultivated such as goldfish, koi fish and comet fish. The aquaponic system can also increase the growth value of length and weight, daily growth rate and survival rate of ornamental fish by 90% - 100%.